2015
DOI: 10.1038/srep17673
|View full text |Cite
|
Sign up to set email alerts
|

Transportation in the Interstitial Space of the Brain Can Be Regulated by Neuronal Excitation

Abstract: The transportation of substances in the interstitial space (ISS) is crucial for the maintenance of brain homeostasis, however its link to neuronal activity remains unclear. Here, we report a marked reduction in substance transportation in the ISS after neuronal excitation. Using a tracer-based method, water molecules in the interstitial fluid (ISF) could be specifically visualized in magnetic resonance (MR) imaging. We first observed the flow of ISF in the thalamus and caudate nucleus of a rat. The ISF flow wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…The ISF pathway is mostly active during sleep when the clearance of harmful metabolites such as beta-amyloid increases two-fold relative to the waking state [74]. By using a newly developed in vivo tracer-based MRI technique, Han and his group demonstrated the drainage of ISF from deep brain regions into the surface of the cerebral cortex [10,46,93]. In addition, they showed that the traced ISF from the caudate nucleus drained into the ipsilateral cerebral cortex along the myelin fiber tracts and then into the subarachnoid space [10].…”
Section: Drainage Of Isf From the Brain Issmentioning
confidence: 99%
“…The ISF pathway is mostly active during sleep when the clearance of harmful metabolites such as beta-amyloid increases two-fold relative to the waking state [74]. By using a newly developed in vivo tracer-based MRI technique, Han and his group demonstrated the drainage of ISF from deep brain regions into the surface of the cerebral cortex [10,46,93]. In addition, they showed that the traced ISF from the caudate nucleus drained into the ipsilateral cerebral cortex along the myelin fiber tracts and then into the subarachnoid space [10].…”
Section: Drainage Of Isf From the Brain Issmentioning
confidence: 99%
“…The calculation of interstitial fluid flow parameters used in this study has been applied in: Transportation in the interstitial space of the brain can be regulated by neuronal excitation [8], the calculation is as below:…”
Section: Calculation Of Interstitial Fluid Flow Parametersmentioning
confidence: 99%
“…The same team of researchers recently found that the cerebral interstitial fluid drainage was partitioned and the new division was completely different from any previous regionalization. [20][21][22] This finding was helpful for exploring the mechanism underlying SDD.…”
Section: Parameters As a New Diagnostic Methods In Therapeutic Evaluatmentioning
confidence: 96%